Evaluation of Gelatin Concentration Variations on the Porosity ofGreen Mussel Shell Hydroxyapatite Scaffolds - Firda Aulia Rahman; Widi Widayat (Journal of Creativity Student, 2026)
The increasing demand for scaffolds in orthopedic applications has driven research into locally sourced biomaterials. Thisstudy evaluates the effect of varying gelatin concentrations (2%, 3%, and 4% w/w) on the porosity of hydroxyapatite (HA) scaffolds synthesized from green mussel shells (Perna viridis). HA was synthesized through a calcination process at a temperature of 900°C, followed by microwave-assisted ultrasonic precipitation, yielding a phase purity of 98.4% as confirmed by X-ray diffraction (XRD). The composite scaffolds were fabricated by mixing HA with type B gelatin at threeconcentrations, molded into cylindrical molds (6 mm diameter × 6 mm height), and dried at 40°C for 24 hours. Porositywas measured using the Archimedes liquid displacement method with 96% ethanol. The results indicated porosity valuesof 57.4% ± 1.68%, 60.2% ± 2.97%, and 58.1% ± 1.15% for gelatin concentrations of 2%, 3%, and 4%, respectively. All formulations exceeded the lower limit of commercial scaffold porosity standards (35–50%), with the 4% formulationapproaching the upper limit of that range. This study demonstrates that HA derived from green mussel shells combinedwith gelatin produces scaffolds with a porosity comparable to commercial products, thereby offering an economical andsustainable alternative for bone tissue engineering applications.